2018
DOI: 10.1016/j.electacta.2017.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of nanostructured Cr-doped hematite with enhanced photoelectrochemical activity

Abstract: Using the easily applicable hydrothermal method Cr-doped hematite thin films have been deposited polycrystalline on conductive glass substrates. The hydrothermal bath consisted of an aqueous solution containing a mixture of FeCl3.6H2O and NaNO3 at pH = 1.5. The samples were introduced in an autoclave and heated for a fixed time at a fixed temperature and then annealed in air at 550ºC. The concentration of the incorporated Cr atoms (Cr 4+ ions) was controlled by varying the concentration of the Cr(ClO4)3 precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 62 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…In many previous studies, the photoelectrochemical activity of photoelectrodes such as TiO 2 and Fe 2 O 3 show signicant enhancement by doping with Cr due to an improvement in charge carrier properties. 33 To the best of our knowledge, the photoelectrochemical studies on the Cr-doped PbS thin lms have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In many previous studies, the photoelectrochemical activity of photoelectrodes such as TiO 2 and Fe 2 O 3 show signicant enhancement by doping with Cr due to an improvement in charge carrier properties. 33 To the best of our knowledge, the photoelectrochemical studies on the Cr-doped PbS thin lms have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the findings described in this perspective can help future works to prepare more efficient hematite nanoceramics to be applied as photoanode, exploiting synergistically an annealing temperature and time that active the material promoting controlled Sn diffusion without damage for the FTO‐glass substrate and, that make it possible to use the advantages of elements like Sn, which act by modifying the interface energies between hematite crystals. In this respect, some elements such as Sb 21 , Nb 108,109 and so on, 23,37,110 have shown similar characteristics to Sn, arising high photocurrent values and showing their potential application on PEC devices. These new evidence and similarities found in the literature and addressing by us show that the interface engineering can be manipulated to improve charge separation and charge transport process, rather than creating trapping sites.…”
Section: Overall Summary and Outlookmentioning
confidence: 95%
“…The annealing process is a common step involved in hematite photoanode manufacturing, considering the different methods that can be used to achieve the hematite phase. As an example, the widely used wet‐based or environmentally friendly routes capable to produce different morphologies generally involve the synthesis of an intermediate phase (such as β‐FeOOH/akaganeite), for which annealing step is necessary to obtain the photoactive phase 23,60 . According to the iron oxide phase diagram, the α‐Fe 2 O 3 phase can be thermodynamically stabilized at the temperature around 390°C, confirmed by thermogravimetric and X‐ray diffraction analysis 56,61 .…”
Section: Sn‐modified Hematite Photoanodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the iron (III) chloride or nitrate solutions are dispersed in aqueous media that contains ammonia to adjust the pH value above 9.0. Later, the solution is heated at high temperatures (≈ 150°C) in an autoclave to decompose the precursors and combine their ions to form new compounds with high homogeneity [50,51]. Hematite nanoparticles were synthesized by [52] by a simple hydrothermal synthesis method using only Fe(NO 3 ) 3 •9H 2 O and NH 3 •H 2 O as raw materials into a Teflon autoclave at different temperatures (80, 100, 120 and 150°C) for 10 h. This research demonstrated that nanoparticles with diameter of 30-100 nm only were produced at temperatures above 120°C in a reaction time within 5 h, occurring an increase in the particles size when longer times were evaluated.…”
Section: α-Hematite (Fe 2 O 3 )mentioning
confidence: 99%